Warrior cardio : the revolutionary metabolic training system for burning fat, building muscle, and getting fit : a complete 12-week training program - Rooney, Martin, 1971- (New York : William Morrow, an imprint of Harper Collins Publishers, 2012)
"A complete 12-week training program"--Cover.
What is cardio, anyway? -- The science of warrior cardio -- Mental cardio -- Warrior performance self-evaluation -- Warrior prehab 15 -- Warrior cardio warmup -- The training for warriors 10 commandments of metabolic training -- Energy circuits -- Hurricane training -- Barbell, dumbbell, and kettlebell circuits -- Body weight circuits -- Specialty strength circuits -- Sprint training -- The finishers -- Core training workouts -- Nutrition for warriors -- Warrior cardio 12-week workout.
"Hundreds of metabolic exercises; dozens of workout routines, including hurricanes, complexes, and body weight and strength circuits; advanced warmup and prehab techniques to prevent injury"--Cover.
Keywords: Exercise; Cardiovascular fitness; Reducing exercises; Physical fitness